2017
DOI: 10.1007/s11325-017-1537-y
|View full text |Cite
|
Sign up to set email alerts
|

A weight-independent association between atypical antipsychotic medications and obstructive sleep apnea

Abstract: While AAP medications are known cause of weight gain as a main risk factor of OSA, our finding demonstrated a weight-independent association between AAP medications and worsening respiration during sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…This result agrees with results obtained from previous studies about effects of AAs on OSA [7,[13][14][15][16]. For instance, Khazaie et al [17] and Rishi et al [18] have compared the severity of OSA in patients taking AAs to that in the control group. After matching the two groups in terms of age, gender, BMI, and NC, it was found that the risk of OSA was significantly higher in patients with schizophrenia using AAs.…”
Section: Smrsupporting
confidence: 91%
“…This result agrees with results obtained from previous studies about effects of AAs on OSA [7,[13][14][15][16]. For instance, Khazaie et al [17] and Rishi et al [18] have compared the severity of OSA in patients taking AAs to that in the control group. After matching the two groups in terms of age, gender, BMI, and NC, it was found that the risk of OSA was significantly higher in patients with schizophrenia using AAs.…”
Section: Smrsupporting
confidence: 91%
“…Although previous definitions of unexpected death in children and youths have excluded unintentional drug overdoses, 56 we included these deaths because the clinical circumstances often are similar to those of deaths due to cardiovascular causes (eg, unexplained death during sleep), and it can be difficult to distinguish the mechanisms post mortem. 61,62 Furthermore, antipsychotics are potent central nervous system depressants 54,55 that can impair respiration [25][26][27][28][29][30] and thus could increase risk of fatal inadvertent overdose with other medications. Our analysis that did not consider overdoses as unexpected deaths showed increased risk of comparable magnitude to that of the primary analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Any condition that disrupts sleep could affect the restorative ability of this state. OSA is one of the more prevalent sleep conditions that leads to sleep fragmentation and hypoxia due to the repetitive occurrence of apnea or hypopnea during sleep …”
Section: Discussionmentioning
confidence: 99%